Exploration and Existence of Local Wisdom as An Effort to Build Sustainable Tourism in Samosir Regency - Pardosi, Jhonson; Putra, Ilham Mirzaya; Pretty, Binur (Universitas Negeri Semarang, 2024)
The development of tourist villages aims to engage the community in the management of tourist destinations and improve their standard of living. The participation of the community, the authentic character of natural attractions, socio-cultural life, and the environment, referred to as local wisdom, provide opportunities for sustainable tourism development. Therefore, it is necessary to increase the interest of the local community in developing attractions, amenities, and tourist accessibility that are complex, flexible, and based on local wisdom, which is a key aspect of tourism development. One of the tourist villages that has diverse local wisdom is Samosir. This study aims to explore and understand the existence of local wisdom found in attractions as strategies for sustainable tourism development. This research is a descriptive-evaluative study with a qualitative approach. Data collection methods in the study were conducted through in-depth interviews, participatory observation, and documentation. Interviews were conducted with informants sequentially and using snowball sampling. Data analysis was carried out step by step, starting from data reduction, data display, and conclusion drawing. Group discussions, triangulation of techniques, and sources were conducted to ensure data credibility. The results of the study indicate a number of local wisdom in the form of attractions that are very rare or even never done. Some cultural heritage is even in an unmaintained condition. The research emphasizes the necessity of increasing local community interest in developing attractions that are multifaceted and rooted in local wisdom. This approach is deemed essential for sustainable tourism development.